Mikhail Rostovtzeﬀ and the Modernization of Antiquity - Zhmud, Leonid (Hyperboreus, 2021)
The introduction of modern notions into the history of the ancient world is not an individual feature of Mikhail Rostovtzeﬀ as an historian but was characteristic of many scholars from the generation of his teachers, and then of his students, and therefore should be viewed against this broader backdrop. With the emergence of economic history, political economists K. Rodbertus and K. Bücher interpreted the economic development of antiquity in terms of the then prevailing notions of progress, and corresponding to this historical period was a very primitive economic order and closed-household economy. Such an archaization of the ancient economy was opposed by Eduard Meyer, an outstanding historian of the ancient world, who not only saw many capitalist elements in antiquity (they were previously discerned by T. Mommsen and later by his students M. Weber, J. Beloch, U. Wilken, R. Pöhlmann etc.) but who in principle rejected the theory of progress in favor of the theory of cycles, or two parallel periods in world history. M. Rostovtzeﬀ shared this theory in his early article “Capitalism and the National Economy in the Ancient World” (1900) which contains many ideas that he later developed in his major works on the social and economic history of Hellenism and the Roman Empire.Evaluating the discussions about Hellenistic and Roman capitalism, we should consider the struggle between primitivists and modernizers to be an integral part of and a powerful stimulus to the scholarly understanding of antiquity, which uses explanatory models. In the second half of the nineteenth century the concept of capitalism had not yet been fully developed (Marx, for example, never used it in his writings) and therefore its scope and content in the works of Rostovtzeﬀ, his associates and critics did in face vary signiﬁcantly. The doctrine of socio-economic formations (slaveholding, feudal, capitalist etc.), habitual to Soviet scholars, was developed only in the 1930s, thus forcing many Soviet historians to abandon their previous views of the historical process, whereas others such as S. Luria continued to write about the struggle of the Greek urban bourgeoisie with the feudal lords.The leading historian of ancient economy after Rostovtzeﬀ, M. Finley, though used Weberian concepts, tended rather to side with the primitivists. In general he insisted on the self-suﬃciency of cells of the ancient economy and denied any Mikhail Rostovtzeﬀ and the Modernization of Antiquity tangible technological progress or economic growth throughout ancient history. By the end of the twentieth century it became clear that the model proposed by Finley needed at very least the same modiﬁcation as Rostovtzeﬀ’s theory. Unlike Rostovtzeﬀ’s theories, his histories remain unsuperceded.